Do-gooder derogation in children: the social costs of generosity - Tasimi, Arber; Dominguez, Amy; Wynn, Karen (Frontiers in Psychology, 2015)
Generosity is greatly valued and admired, but can it sometimes be unappealing? The current study investigated 8- to 10-year-old children’s (N=128) preference for generous individuals, and the effects of social comparison on their preferences. In Experiment 1, children showed a strong preference for a generous to a stingy child; however, this preference was significantly reduced in a situation that afforded children a comparison of their own (lesser) generosity to that of another child. In Experiment 2, children’s liking for a generous individual was not reduced when that individual was an adult, suggesting that similarity in age influences whether a child engages in social comparison. These findings indicate that, by middle childhood, coming up short in comparison with a peer can decrease one’s liking for a generous individual.